Tinjauan Perspektif Ekonomi dan Nonekonomi Perempuan Bali yang Bekerja di Sektor Publik: Studi Konflik Peran - Saskara, Ida Ayu Nyoman; .., Pudjihardjo; Maskie, Ghozali; suman, agus (Jurnal Aplikasi Manajemen, 2012)
The purpose of this study is to examine: (1) the influence of culture on the economy and work environment, (2) the influence of the social economy, (3) the influence of economic and noneconomic (cultural, work environmental, and social) on role conflict, (4 ) behavior of Balinese women in resolving conflicts. Total respondents were 216 people. Data were analyzed by PLS method (Partial Least Square) and descriptive qualitative. The research results showed that Balinese women's role conflict significantly influenced by cultural and work environment variables. Culture also has significant effect on the economy and work environment variables. Economy variables has significant effect on social variable. While the economic and social variables are not shown to increase role conflict, Balinese women who workin public sector experience behavioral changes.